2013
DOI: 10.1558/cj.v19i3.551-561
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Online Quizzes on Learning Japanese

Abstract: An assistant professor of Japanese and an instructional technologist teamed up to create online review quizzes for students of intermediate Japanese at Gettysburg College. Because of the convenience of online delivery, these quizzes were well suited to the needs of today's liberal arts students who often participate in many extracurricular activities. Student use of these quizzes increased over the course of the semester, and the benefits to them were measurable, especially in those students who had performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 3 publications
1
1
0
1
Order By: Relevance
“…Kabata et al (2005) and Alqahtani and Rajkhan (2020) also reported that it is what the instructors do (or do not) during online classes that will create a positive (or negative) modelling behaviour to the learners. This is also reported by Itoh and Charles (2002) who found that students felt comfortable discussing with their peers online to prepare for exams.…”
Section: Learning From Observationsupporting
confidence: 57%
See 1 more Smart Citation
“…Kabata et al (2005) and Alqahtani and Rajkhan (2020) also reported that it is what the instructors do (or do not) during online classes that will create a positive (or negative) modelling behaviour to the learners. This is also reported by Itoh and Charles (2002) who found that students felt comfortable discussing with their peers online to prepare for exams.…”
Section: Learning From Observationsupporting
confidence: 57%
“…These are factors that made it less successful and factors that can make learning Japanese online successful for the learners. The study by Itoh and Charles (2002) to explored students' perception on taking quizzes online. The quizzes were given to students from liberal arts in a college.…”
Section: Learning Japanese Onlinementioning
confidence: 99%
“…Tetapi bahasa Jepang terutama kanjinya, sulit dipelajari dan merupakan tantangan tersendiri bagi mereka yang terbiasa menggunakan bahasa latin (Everson, 2011). Oleh karena itu banyak metode yang digunakan untuk membantu orang yang ingin mempelajari bahasa Jepang salah satunya adalah dengan kuis online, di mana metode tersebut dapat meningkatkan pengetahuan karena fleksibilitasnya yang dapat diakses kapan saja dan tidak terikat waktu untuk belajar (Itoh & Hannon, 2002). Selain itu terdapat juga metode mempelajari kanji dengan bantuan komputer yang disebut computer assisted language learning (CALL) yang terbukti meningkatkan kemampuan untuk belajar kanji (Chikamatsu, 2003).…”
Section: Pendahuluanunclassified